Factors Employying The Popular Heritage In The Resistant Palestinian Poetry (Journal of Hama University, 2021)
This study aims to try to uncover factors that employ popular heritage in Palestinian resistance poetry, And The reasons that drive Palestinian poets to use folklore in their poems, And The implications of this employment include a semantic and epistemological enrichment of poetic texts that contain among their vocabulary heritage elements and popular symbols, in addition to giving them an aesthetic character. After reviewing a group of specialized researches in the field of popular heritage and employing it among a group of Palestinian poets, the research was able to find out a set of factors that pushed Palestinian poets to employ heritage in their poems. Among them are political factors related to the political situation in Palestine from the Nakba to the present time, and national factors related to preserving the Arab national and Palestinian national identity that the occupation is working to eradicate, In addition to artistic factors that in turn are based on two main factors: the poets ’awareness of the richness of heritage and its richness with popular models and symbols that can enrich the poem with suggestive and expressive cards that have no limits, and the second factor relates to the poet’s desire and his tendency to impart a kind of objectivity and drama to his lyric passion outside in This is what prevailed in the Arabic poem for a long period of self-sufficiency. As for the fourth factor of the motives for employing heritage, it relates to cultural factors that helped him to use heritage in his poetry technically, through which the poet was able to move from the stage of "recording heritage" or "expressing it" to the stage of "employing heritage" or "expressing it."Finally, the importance of this study comes from the fact that it examined the issue of popular heritage penetrated in the hearts of people, and revealed the importance and motives of its use in Palestinian resistance poetry, and its transformation into a weapon of the Palestinian resistance